Beberapa isu haraki di dalam karya-karya hadis Sayyid Muhammad Nuh - Muhammad Arif Yahya (Universiti Kebangsaan Malaysia, 2014)
Sayyid Muhammad Nuh is a prominent ‘haraki’ figure and has produced a number of works in the field of hadith studies. He has been involved in the dakwa movement of the Muslim Brotherhood which influenced his approach in the production of his works, in terms of the ‘haraki manhaj’ and methods. Almost all the works of Sayyid Muhammad Nuh emphasized issues of dakwa and tarbiyah, whether in the field of tafsir, hadith, history and issues of the Muslims’ society. Moreover, the issues that he highlighted were practical and the application of ‘haraki’ approach in production of writings brought about significant lesson to the dakwa movement, including the ones in the field of hadith. The author presents three of his works in the field of hadith which have been among the most referred and widely read in the dakwa circle, including the dakwa movement in Malaysia. His selected works in the field of hadith are ‘Tawjihat of the Prophet `ala al-Tariq’ (Hadiths of Guidance on the Dakwa Path), ‘Manhaj al -Rasul fi Ghars Ruh al-Jihad fi Nufus Ashabih’ (The Messenger’s Approach in Inspiring Spirit of al-Jihad in the Companions), and ‘Min Akhlaq al-Nasr fi Jiyl al-Sahabah’ (Winning Attitudes in the Generation of the Companions). Through this article, the authors highlights a number of ‘haraki’ issues based on the works of Sayyid Muhammad Nuh and the important lessons that he has highlighted for the people of dakwa in facing the dakwa path, based on the hadith of the Messenger.